MODERN LINGUISTIC APPROACHES TO THE STUDY OF LITERARY TRANSLATION - Ozoda Abduhamidova Abduhamid qizi (Modern American Journals, 2025)
This article examines literary translation within the framework of modern linguistic paradigms, focusing on cognitive, functional, pragmatic, and semiotic approaches. The study reveals how these theories expand the understanding of translation beyond linguistic equivalence, viewing it as a complex act of cross-cultural communication and artistic interpretation. The paper argues that literary translation should be considered both a linguistic and cognitive process that reconstructs meaning, style, and aesthetic value across languages.
Keywords: Literary translation, modern linguistics, cognitive linguistics, functional approach, pragmatics, semiotics, equivalence, cross-cultural communication.